From Private Autonomy to State Regulation: Shifting Boundaries in Civil Law - Samsidar Samsidar (Leges Privatae, 2025)
Classical civil law is fundamentally grounded in the doctrine of private autonomy, which positions individual free will as the primary source of legal obligations. However, the evolution of the welfare state, the expansion of regulatory governance, and the increasing protection of public interests have significantly altered this paradigm. In Indonesia, this transformation has produced normative ambiguity regarding the boundary between freedom of contract and state regulatory authority, particularly due to inconsistencies between the Civil Code and sectoral regulatory statutes. This article employs normative legal research using statute, conceptual, and case approaches to examine the shifting relationship between private autonomy and state regulation in civil law. The analysis demonstrates that unstructured regulatory intervention risks undermining legal certainty and diluting the normative core of civil law, while absolutist private autonomy is no longer tenable in a modern regulatory state. This article argues for a reconstruction of civil law based on conditional private autonomy, supported by proportionality and accountability principles, in order to balance private interests and public objectives in a constitutionally coherent manner.